Identification of a candidate gene for Re, the factor determining the red leaf phenotype in ornamental kale using fine mapping and transcriptome analysis. (10th September 2017) - Ren, Jie; Fu, Wei; Du, Jiangtao; Hou, Ailin; Liu, Zhiyong; Feng, Hui
Abstract: The red inner leaf phenotype of ornamental kale is due to anthocyanin accumulation and is an important agronomic trait. This phenotype is controlled by a single dominant nuclear gene, Re . An F2 mapping population from a cross between red leaf and white leaf lines was developed, and Re was found to be located between BYIn3 and C09‐In51 on chromosome nine (C09) at a distance of 0.003 and 1.8 cM, respectively. Twenty‐six genes were identified in this region, but none were related to the anthocyanin biosynthesis pathway. On the basis of information from Ensembl Plants, transcriptome analysis of the mapping parents and identification of anthocyanin biosynthetic genes in Brassica oleracea, we predicted that Bol035269, which encodes dihydroflavonol 4‐reductase, is a candidate gene for Re, and is located on Scaffold000035_P2. Sequencing of the mapping parents revealed a 2, 400‐bp insertion and a 124‐bp deletion in the white leaf line. Quantitative real‐time PCR showed that Bol035269 in the red leaf line was expressed at an approximately 1, 045‐fold higher level than in the white leaf line.